If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 6x = 6 + 5x Solving -10 + 6x = 6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -10 + 6x + -5x = 6 + 5x + -5x Combine like terms: 6x + -5x = 1x -10 + 1x = 6 + 5x + -5x Combine like terms: 5x + -5x = 0 -10 + 1x = 6 + 0 -10 + 1x = 6 Add '10' to each side of the equation. -10 + 10 + 1x = 6 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = 6 + 10 1x = 6 + 10 Combine like terms: 6 + 10 = 16 1x = 16 Divide each side by '1'. x = 16 Simplifying x = 16
| 5=x-5+3 | | a+5=-2+8a | | 7b^2+9b+10=8 | | 3(x+9)=2x-(6-x) | | 3y=37(2x) | | an=11-3 | | -15+4x=7+3x | | 7y-8=16 | | 5(1-8m)=5-3m | | 7x-9+8x-13= | | x^5-9x^4+18x^3= | | -2x+3=1-3x | | 8x-27=2x+33 | | 8c+1b=12.89 | | 2v-v=12-v | | 8x-31=19+3x | | 4x-3(x-2)=27 | | x^2+x^4=90 | | -4x-8(3-5x)=192 | | 12xz^2+36x^2z-120x^3=0 | | 7r^2+10r+3=0 | | 1+5p=-4+6p | | 25x^2+40x+80=0 | | x+3x-1+.5x+13=57 | | -8x-7=10-9x | | 15x^2+34x-6=0 | | 3x=12z | | (8+w)54=5 | | 7-n=1-4n | | d+d+2d= | | -3(-4-6)+7(-x+5)=-8 | | 5x-69=74-8x |